Growth and instability of Chhattisgarh’s non-basmati rice - SARITA GHIDODE (ORYZA-An International Journal of Rice, 2026)
The "Rice Bowl of India," Chhattisgarh, contributes substantially to the country’s Non-Basmati rice production, yet remains underrepresented in export markets. This paper examines the growth performance, instability, and trade dynamics of Non-Basmati rice in Chhattisgarh from 2012-13 to 2023-24. The findings indicate a notable increase in production and yield, particularly during 2020-2023. Although the area under cultivation expanded only marginally (CAGR: 1.02%), there were statistically significant increases in production (3.89%) and yield (2.84%). Export performance showed high volatility, with 2023 recording the highest export value (` 2,846.59 million). To translate Chhattisgarh’s strong production base into sustainable export gains, targeted policy interventions are required. Strengthening post-harvest handling and milling infrastructure is critical to ensure export-grade quality and reduce losses. Establishing specialized export clusters and logistics hubs in major rice-producing regions can enhance market connectivity. Improving SPS compliance, quality testing facilities, and certification systems will support adherence to international standards. Additionally, capacity building for farmers, FPOs, and millers on export protocols and value addition is essential for enhancing global competitiveness.